Electrical properties of photo-crosslinked fullerene thin films. (22nd September 2017) - Kim, Jong H.; Cho, Namchul
ABSTRACT: In this work, we report the fullerene thin films incorporated with a bis(perfluorophenyl) azide based photo-crosslinker. We show that introducing the photo-crosslinker into the fullerene films (LT-S9079 from Lumtec) significantly increases electrical conductivity after photo-crosslinking. We used X-ray diffraction (XRD) measurements to confirm that the crosslinking of LT-S9079 produces more ordered structure, showing that the photo-crosslinker can be a good bridge material for charge carrier transport after crosslinking. This result shows that it can be used in complicated and highly integrated optoelectronic semiconductor devices particularly those require orthogonal processes.